Knowledge and rural development: Dialogue at the heart of innovation - Clavel, D. (CTA / Quae, 2011)
Faced with the clear failure of public development aid to reduce inequalities and hunger, especially in Africa, wide consensus has been reached on the need for a new approach to improve agricultural production. The African initiatives described in this book illustrate innovative development methodologies where dialogue, the active participation of communities and consideration of local knowledge are the basic principles.